Trump and us : what he says and why people - Hart, Roderick P. (Cambridge, United Kingdom Cambridge University Press, 2020)
The book offers the first systematic rhetorical analysis of Trump's 2016 campaign and early presidency, using text analysis and archives of earlier presidential campaigns to uncover deep emotional undercurrents in the country and provide historical comparison. Trump and Us pays close attention to the emotional dimensions of politics, above and beyond cognition and ideology. Hart argues it was not partisanship, policy, or economic factors that landed Trump in the Oval Office but rather how Trump made people feel.
Keywords: Cultura política -- EEUU; Comunicación en política -- EEUU -- Siglo 21; Prensa y política -- EEUU